Horizontal drains in residual soil slopes - Santoso, Vera Amalia (2011)
Horizontal drains have been used extensively for preventive and repair works of slopes. Horizontal drains have been found to be effective in lowering groundwater table to increase the stability of slopes. The ideal location of horizontal drain is at the toe of the slope in order to optimize the thickness of unsaturated zone from the horizontal drain to the ground surface. However, the ideal length of the horizontal drain has not been fully investigated, particularly for residual soil slopes. In this study, the effectiveness of different lengths of horizontal drains in sedimentary and granitic residual soils is investigated. Typical soil-water characteristic curves and permeability functions of the soils were used in performing seepage analyses of water flow through unsaturated soil slope with horizontal drains. It appears that the length of horizontal drain affects water flow through unsaturated soil slope and consequently stability of the slope under heavy rainfall conditions. Results of slope stability analyses indicate that the horizontal drain installed to the critical slip surface provides the ideal length of horizontal drains in residual soil slopes. In addition, soil properties also influence the effectiveness of horizontal drains in maintaining stability of slopes.